Contextual attributes promote or hinder self-regulated learning: A qualitative study contrasting rural physicians with undergraduate learners in Japan. (4th March 2018) - Matsuyama, Yasushi; Nakaya, Motoyuki; Okazaki, Hitoaki; Leppink, Jimmie; van der Vleuten, Cees
Abstract: Background and objectives: Previous studies support the notion that East Asian medical students do not possess sufficient self-regulation for postgraduate clinical training. However, some East Asian physicians who are employed in geographically isolated and educationally underserved rural settings can self-regulate their study during the early phase of their postgraduate career. To explore the contextual attributes that contribute to self-regulated learning (SRL), we examined the differences in self-regulation between learning as an undergraduate and in a rural context in East Asia. Methods: We conducted interviews and diary data collection among rural physicians ( n = 10) and undergraduates ( n = 11) in Japan who undertook self-study of unfamiliar diseases. We analyzed three domains of Zimmerman's definition of SRL: learning behaviors, motivation, and metacognition using constructivist grounded theory. Results: Rural physicians recognized their identity as unique, and as professionals with a central role of handling diseases in the local community by conducting self-study. They simultaneously found themselves being at risk of providing inappropriate aid if their self-study was insufficient. They developed strategic learning strategies to cope with this high-stakes task. Undergraduates had a fear of being left behind and preferred to remain as one of the crowd with students in the same school year. Accordingly, they copied the methods of other students for self-study and used monotonous and homogeneous strategies. Conclusions: Different learning contexts do not keep East Asian learners from being self-regulated. Awareness of their unique identity leads them to view learning tasks as high-stakes, and to initiate learning strategies in a self-regulated manner. Teacher-centered education systems cause students to identify themselves as one of the crowd, and tasks as low-stakes, and to accordingly employ non-self-regulated strategies.